Perbedaan Penerapan Derivative Action Di Indonesia Sebagai Negara Civil Law Dibandingkan Dengan Negara-Negara Penganut Sistem Hukum Common Law (Studi Putusan Perdata Nomor 02/Pdt.G/2010/PN.Jkt.Sel) - Shobah, Shofia (Jurnal Hukum & Pembangunan, 2018)
The protection of minority shareholders within the company is one importance thing given the likelihood of their rights being violated by the actions of the board of directors. In the concept of the company, shareholders are passive parties who do not participate in the management of the company, thus causing the shareholders vulnerable to deviations. The rights of the company's shareholders are very important for the concept of Corporate Governance. Shareholders are not corporate organs because the company's organs are General Meeting of Shareholders (GMS). The Board of Directors may decide to run the company as long as it does not violate Companies Acts. The Board of Directors must act in good faith and for the best interests of the corporation, this is where the importance of protecting minority shareholders is exercised. One of the real manifestations of such protection is through a derivative lawsuit that allows minority shareholders to fight for their rights within the company